Thesis project archive system (T-PAS) - Shahrul Nazmi, Ismail (2013)
Thesis is the report should be made by final year students in the Faculty of Computer Systems & Software Engineering (FSKKP), Universiti Malaysia Pahang. There are two types of thesis report namely research and technical. Each thesis report must be bound kept in the thesis room. The thesis then will use as a general reference thesis for FSKKP’s students. However, there are constraints in terms of the arrangement and search methods to find each thesis reports stored in the room. This will make it difficult for students to find topics that they wish to use a reference. There is also has time constraint problems faced by students and difficult for them to go into the room at every times. Safety of each thesis report also cannot be guaranteed because there is no method that can ensure the printed report or thesis project was included in the compact disc can hold out against damage or theft. Therefore, Thesis Project Archive System (T-PASS) was developed to help students more easily to find their desired report. Students can enter the system at every time. In addition, the safety report is also more secure as more systematic management methods in the T-PAS can create data integrity in it. To create a complete system, T-PAS will be developed using the Waterfall System Development Life Cycle (SDLC). PHP programming language and MySQL has been chosen as the need to develop this system. By using storage approach using database system, it will prove to be helpful to manage the report thesis in FSKKP for their students more effectively